Calf, Dam and Sire Factors Affect Birth Weight of Gir Calves - Parikh, Suryakant S.; Savaliya, Bhagvanji D.; Patbandha, Tapas K.; Makwana, Rinkesh B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Birth weight data of Gir calves (n = 1116) spread over 9 years (2011-2019) were used to assess the influence of calf, dam, and sire factors on the birth weight of calves. Various calf factors, viz., period, month, season, and sex of calf; dam factors, viz., age, parity and gestation period and sire factors of Gir cattle were considered for the study. The overall mean birth weight of Gir calves was 22.29 ± 0.10 kg. There was a significant effect of the period (p ≤0.05), month (p ≤0.05), and season (p ≤0.05) of calving on calf birth weight. The weight of Gir calves at birth was lower during the rainy season and higher during the winter season (p ≤0.05). Male calves had 10 % (2.2 kg) higher birth weight than their female counterparts (p ≤0.05). There was a significant effect of age (p ≤0.05) and parity (p ≤0.05) of a dam on calf birth weight. The gestation period also had a significant (p ≤0.05) effect on birth weight. The birth weight was significantly (p ≤0.05) influenced by the service sire. The heritability estimate was 0.132 for the birth weight of Gir calves, which indicated low heritability. The results showed that calf, dam, and sire factors markedly influenced birth weight, and better managemental interventions during the last trimester of pregnancy could improve the birth weight of calves in Gir cattle.